THE ROLE OF TRADITIONAL APPRENTICESHIP IN PRESERVING THE CULTURAL HERITAGE OF FOLK ART (Web of Teachers: Inderscience Research, 2025)
This article examines the essential role of traditional apprenticeship in preserving the cultural heritage of folk art. It argues that the master–apprentice model is not only a method of transmitting technical skills but also a vital mechanism for maintaining cultural identity, aesthetic values, and intergenerational continuity. The study highlights the historical functions of apprenticeship, its contribution to social and cultural integration, and the modern threats posed by globalization and commercialization. It underscores the irreplaceable value of direct, personal instruction in safeguarding authentic craft traditions and cultural meanings. The article also discusses innovative approaches such as museum-based workshops, digital documentation, and international residencies that can support, but not replace, the traditional system. Recommendations are offered to strengthen apprenticeship practices through state support, integration into formal education, international cooperation, and mechanisms for protecting intangible cultural heritage.